2013
DOI: 10.3892/mco.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

Early response to neoadjuvant chemotherapy in advanced esophageal cancer evaluated by computed tomography predicts the utility of a second cycle of chemotherapy

Abstract: Abstract. Multi-course neoadjuvant chemotherapy (NACT) followed by surgery is a promising treatment for advanced esophageal cancer. However, non-responders may continue to receive ineffective treatment, since there are no definitive criteria for early discontinuation of NACT. In this study, we analyzed 103 advanced esophageal cancer patients treated with 2 cycles of NACT followed by surgery. Patients with >20% decrease in the size of the primary tumor as evaluated by computed tomography (CT) following the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In previous studies, we substituted adriamycin for epirubicin in combination with CF (ACF regimen) for neoadjuvant chemotherapy and reported good efficacy [11,13] . Recently, docetaxel plus CF (DCF regimen) has been reported to achieve a notably high response rate in unresectable metastatic gastric cancer and head and neck squamous cell carcinoma [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we substituted adriamycin for epirubicin in combination with CF (ACF regimen) for neoadjuvant chemotherapy and reported good efficacy [11,13] . Recently, docetaxel plus CF (DCF regimen) has been reported to achieve a notably high response rate in unresectable metastatic gastric cancer and head and neck squamous cell carcinoma [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Cancers that start in the esophagus are much more common in men than in women and many of these cancers are linked to tobacco or alcohol use, or to excess body weight [23]. Esophageal tumors usually lead to dysphagia (difficulty swallowing), pain and other symptoms [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal tumors usually lead to dysphagia (difficulty swallowing), pain and other symptoms [23,24]. Small and localized tumors can be treated surgically with curative intent [24].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that neoadjuvant therapy improves the prognosis of patients with ESCC. Furthermore, it is well known that patients with surgically‐resected specimens assessed as having pathological tumor regression after chemotherapy show improved survival rates …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well known that patients with surgically-resected specimens assessed as having pathological tumor regression after chemotherapy show improved survival rates. [4][5][6] "The response evaluation criteria in definitive chemoradiotherapy (dCRT) for primary lesion using endoscopy" (dCRT criteria) was developed as part of the Japanese classification of esophageal cancer to specifically determine patients with complete response (CR) after dCRT, which is associated with favorable long-term outcomes (Table S1). 7,8 These criteria have also been applied for the evaluation of primary lesions after nCT.…”
Section: Introductionmentioning
confidence: 99%